(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Caesarean Scar Ectopic Pregnancy (CSEP) is a rare form of extrauterine pregnancies which is usually life theatening. It occurs when pregnancy implants in a caesarean scar. Though rare form, the number of CSEP incidence is in rising trend due to global increasing numbers of cesarian section deliveries comparing with other form of ectopic pregnancies. CSEP poses a greater risk to maternal haemorrhage and even death. The purpose of the study to disseminated our knowledge and experience of clinical characteristics, presentation and treatment about the case report for the readers as future references. Case Presentation: On 19th May 2022 a third gravida patient with the history of two previous caesarean section came to the Islamic Bank Hospital Agrabad, Chattogram with9 weeks of amenorrhoea. She had expressed to discontinue her pregnancy. According to the USG a caesarean scar ectopic pregnancy was diagnosed which was corresponding to 6+ weeks of gestation and was advised for TVS and HCG. On 2nd June 2022 the patient admitted in Chattogram Maa-O-Shishu Hospital Medical College. Her TVS findings showed endophytic types of CSEP with her HCG was 144730 MIU/ml. Though different modalities of treatments are available, the surgical excision with effective haemostasis was done with preserving the uterus successfully. Post operative period was uneventful. Two units of blood were transfused to correct anaemia. Histopathology reports revealed decidual changes with chorionic villi. Conclusion: Although CSEP is a rare condition. An early diagnosis and well-planned treatment can save uterus, preserve fertility as well as can prevent mortality and morbidity. JCMCTA 2022 ; 33 (2) : 140-143